2015
DOI: 10.5590/jerap.2015.05.1.04
|View full text |Cite
|
Sign up to set email alerts
|

A Framework for Evaluating Learning Progressions on Features Related to Their Intended Uses

Abstract: In recent years, learning progressions (LPs) have captured the interest of educators and policy makers. There have been numerous efforts to develop LPs aligned to college and career readiness standards, to unpack these standards, and to provide more clarity on the pathways students follow to reach them. There is great variation, however, in the structure, content, and features of LPs, and these have implications for the LP’s most appropriate use. The purpose of this research was to devise a framework to unders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…The second goal was to enhance student participation through the construction of a science identity and development of efficacy regarding engineering so that students can function as agents of change within their communities. The design of each anchor in the learning progression was aligned with Kobrin et al ( 2015 ) discussion of how the anchors should progress students in addressing preconceptions in the first or entry anchor, provide an intermediate level for cognitive and conceptual development, and determine explicit objectives that demonstrate that learning has occurred within the last anchor. In addition to conceptual development, we used a bottom-up approach to look at the progression of participation in engineering practices and the development of epistemic agency within the community.…”
Section: Methodological Approachmentioning
confidence: 99%
“…The second goal was to enhance student participation through the construction of a science identity and development of efficacy regarding engineering so that students can function as agents of change within their communities. The design of each anchor in the learning progression was aligned with Kobrin et al ( 2015 ) discussion of how the anchors should progress students in addressing preconceptions in the first or entry anchor, provide an intermediate level for cognitive and conceptual development, and determine explicit objectives that demonstrate that learning has occurred within the last anchor. In addition to conceptual development, we used a bottom-up approach to look at the progression of participation in engineering practices and the development of epistemic agency within the community.…”
Section: Methodological Approachmentioning
confidence: 99%
“…According to Shavelson and Kurpius [13], there are three essential elements of learning progression. These include the notion of learning as developmental that happens over time, the importance of instruction in facilitating students' learning as they progress from novice to expert in understanding concepts, and empirical research and validation [14].…”
Section: Learning Progressionmentioning
confidence: 99%
“…Finally, the design principles of this study are in line with those of Kobrin et al (2015), except that their expert study only proposed a fine-grained structure and our study also identified the need for a big picture that shows how current teaching fits into the larger LT. This finding presents the possibility to investigate whether an LT visualization can be developed for multiple purposes simultaneously.…”
Section: Conclusion and Discussionmentioning
confidence: 56%
“…This definition emphasizes that empirical research is used to validate the ways in which students' reasoning develops (Corcoran et al, 2009), that knowledge and skills in a learning domain are connected , and that learning is conceived as a coherent process of increasing sophistication (Corcoran et al, 2009;. This differs from standards or curriculum frameworks that generally describe discrete objectives for the end of a grade level based on conventional wisdom and expert consensus (Bailey & Heritage, 2014;Kobrin, Larson, Cromwell, & Garza, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation